2021
DOI: 10.1590/1807-3107bor-2021.vol35.0021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clinical use of NiTi reciprocating instruments on cyclic and torsional resistance, and on roughness

Abstract: The aim of the present study was to evaluate the cyclic fatigue, torsional resistance and surface roughness of Reciproc R25 instruments in four different situations, namely as new instruments and as instruments tested after clinical preparation of one, two or three maxillary molars with four root canals. The total time required to perform each root canal preparation was recorded. Cyclic fatigue resistance was determined by the time to fracture using a customized testing device (n = 10 per group). The torsional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Interestingly, although profilometry analysis revealed a change in instrument roughness after their use, this difference was significant only in the XPS group, but the values of roughness parameters generally increased after the first and decreased after the second use in all groups. These observations are partly in accordance with the results published by Moreira et al [9], who concluded that the clinical use of Reciproc decreased the surface roughness. In some previous studies, using optical profilometry, the roughness values of reciprocating instruments increased after their use [6, 15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, although profilometry analysis revealed a change in instrument roughness after their use, this difference was significant only in the XPS group, but the values of roughness parameters generally increased after the first and decreased after the second use in all groups. These observations are partly in accordance with the results published by Moreira et al [9], who concluded that the clinical use of Reciproc decreased the surface roughness. In some previous studies, using optical profilometry, the roughness values of reciprocating instruments increased after their use [6, 15].…”
Section: Discussionsupporting
confidence: 93%
“…The overall incidence of file separation is 2.27%, with a higher incidence associated with rotary motion (2.43%) than with reciprocating motion (1.0%) [3]. The surface wear and fracture resistance of various instrumentation systems have been investigated by analysing the surface roughness and cyclic fatigue (CF) resistance of both intact and used NiTi instruments [4][5][6][7][8][9]. At the same time, with advances in manufacturing methods and new alloys, the fatigue life, centring ability and canal transportation of the NiTi files have been improved [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasize that the cost can be decreased with repeated use of the instruments. In contrast, as the number of uses increases, the chance of instrument fracture and the average time required for the instrumentation of the canal will increase, as the file will experience reduced surface roughness, fatigue, and cutting efficiency, as confirmed by other studies as well [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 72%